(3GdEbfGY aj GdbQGAGJ GdSHYs - (3CHh LYaQ CMeO Hf Ydj Hf HGPT GdfMhj,J (B546 (3g` s
(3ChdgG (B:s
(3hEfi JCedJ cJGHi GdTjNjf GdGeGejf CHj eMeO eci GHf CHj WGdH GdbjSi hCHi YeQh YKeGf Hf SYjO GdbQTi QVi Gddg YfgeG GdJHUQI hGdJjSjQ ESJNQJ Gddg JYGdi ai Ve GdTcd Edi Tcdg s
(3BNQgG (B:s
(3bGd cHQ MJi JNJe eY GdNGJeI cd ShQg aEfi bQCJ Ydi THd Hf YHGO hYdi YHO s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B140s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs